Shifting Perspectives in Polar Research: Global Lessons on the Barriers and Drivers for Securing Academic Careers in Natural Sciences - Figuerola, Blanca; Valiente, Nicolas; Barbosa, Andres; Brasier, Madeleine J.; Colominas-Ciuró, Roger; Convey, Peter; Liggett, Daniela; Fernández-Martínez, Miguel Angel; Gonzalez, Sergi; Griffiths, Huw J.; Jawak, Shridhar D.; Merican, Faradina; et al. (Frontiers in Ecology and Evolution, 2021)
The polar regions provide valuable insights into the functioning of the Earth’s regulating systems. Conducting field research in such harsh and remote environments requires strong international cooperation, extended planning horizons, sizable budgets and long-term investment. Consequently, polar research is particularly vulnerable to societal and economic pressures during periods of austerity. The global financial crisis of 2008, and the ensuing decade of economic slowdown, have already adversely affected polar research, and the current COVID-19 pandemic has added further pressure. In this article we present the outcomes of a community survey that aimed to assess the main barriers and success factors identified by academic researchers at all career stages in response to these global crises. The survey results indicate that the primary barriers faced by polar early and mid-career researchers (EMCRs) act at institutional level, while mitigating factors are developed at individual and group levels. Later career scientists report pressure towards taking early retirement as a means of institutions saving money, reducing both academic leadership and the often unrecognized but vital mentor roles that many play. Gender and social inequalities are also perceived as important barriers. Reorganization of institutional operations and more effective strategies for long-term capacity building and retaining of talent, along with reduction in non-research duties shouldered by EMCRs, would make important contributions towards ensuring continued vitality and innovation in the polar research community.